Satanic whispers: Milton's Iblis and the "Great Sultan". Issue 1 (2nd January 2017) - Al-Akhras, Sharihan; Green, Mandy
ABSTRACT: The seventeenth century witnessed a burgeoning of Arabic studies in the universities and the first English translation of the Turkish Alcoran (1649). However, John Milton has generally been passed over in scholarship concerned with the influence of Arabic studies on early modern literature. Yet, since Islam was recognized as one of the great challenges to the true faith at this time, it would be surprizing if its presence were not felt in Milton's great Protestant epic, Paradise Lost . This article hopes to demonstrate how, at times, Milton's depiction of Satan is intriguingly similar to that of his Qur'anic counterpart Iblis. Without overstating the Qur'anic influence, it offers for consideration a number of instances where the outlines of both fallen angels converge in a way that amplifies understanding of particular narrative moments in the poem. Readers familiar with the way Milton appropriates narrative paradigms from classical epic, both to enhance Satan's characterization and subvert classical conceptions of heroism, might find it interesting to speculate whether he also deployed a similar, though not so extensive, strategy in relation to Islam, drawing on Qur'anic imagery in the cause of Christian truth, while at the same time tarring Muhammad's teachings as impostures of Satan.